2015
DOI: 10.1104/pp.15.00635
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing of exocyst genes in the stigma impairs the acceptance of compatible pollen in Arabidopsis

Abstract: Initial pollen-pistil interactions in the Brassicaceae are regulated by rapid communication between pollen grains and stigmatic papillae and are fundamentally important, as they are the first step toward successful fertilization. The goal of this study was to examine the requirement of exocyst subunits, which function in docking secretory vesicles to sites of polarized secretion, in the context of pollen-pistil interactions. One of the exocyst subunit genes, EXO70A1, was previously identified as an essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 84 publications
0
47
1
Order By: Relevance
“…Tryphine is a complex mixture of lipids, proteins, glycoconjugates and pigments (Piffanelli et al, 1998;Hernandez-Pinzon et al, 1999) that confers adhesive properties to the grain, provides a conduit for water to pass from the stigma to effect pollen hydration and, importantly, carries factors that determine compatibility (Dickinson, 1995;Safavian & Goring, 2013). Pollen access to stigmatic water requires targeted secretion in the stigma immediately adjacent to a compatible pollen grain (Dickinson, 1995) and it is now well established that in the Brassicaceae this involves exocyst-mediated tethering of secretory vesicles to the stigmatic plasma membrane (Samuel et al, 2009;Safavian & Goring, 2013;Safavian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tryphine is a complex mixture of lipids, proteins, glycoconjugates and pigments (Piffanelli et al, 1998;Hernandez-Pinzon et al, 1999) that confers adhesive properties to the grain, provides a conduit for water to pass from the stigma to effect pollen hydration and, importantly, carries factors that determine compatibility (Dickinson, 1995;Safavian & Goring, 2013). Pollen access to stigmatic water requires targeted secretion in the stigma immediately adjacent to a compatible pollen grain (Dickinson, 1995) and it is now well established that in the Brassicaceae this involves exocyst-mediated tethering of secretory vesicles to the stigmatic plasma membrane (Samuel et al, 2009;Safavian & Goring, 2013;Safavian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because Brassica plants have dry stigmas, the pollen grain has to obtain water from the stigmatic papilla for germination and the growth of pollen tube [19]. Several recent studies have revealed that the stigma defect could be rescued under low-or high-humidity growth conditions, and demonstrated that Exo70A1 was indispensable in the regulation of stigmatic papilla water secretion and pollen hydration [17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Arabidopsis (Arabidopsis thaliana) and maize (Zea mays) have implicated the exocyst in the regulation of pollen tube and root hair growth, seed coat deposition, response to pathogens, cytokinesis, and meristem and stigma function (Cole et al, 2005;Synek et al, 2006;Hála et al, 2008;Fendrych et al, 2010;Kulich et al, 2010;Pecenková et al, 2011;Safavian and Goring, 2013;Wu et al, 2013;Safavian et al, 2015;Zhang et al, 2016). The growth arrest of pollen tubes in sec8, sec6, sec15a, and sec5a/sec5b single and double mutants (Cole et al, 2005;Hála et al, 2008) or following treatment with the EXO70 inhibitor ENDOSIDIN2 (Zhang et al, 2016), and of root hairs in maize root hairless1 (rth1) SEC3 mutant (Wen et al, 2005), the inhibition of seed coat deposition in the sec8 and exo70A1 mutants (Kulich et al, 2010), and stigmatic papillae function in exo70A1 mutant plants (Safavian and Goring, 2013;Safavian et al, 2015) have implicated the exocyst in polarized exocytosis in plants. Given their function, it was likely that exocyst subunits could be used as markers for polarized exocytosis.…”
mentioning
confidence: 99%